Mencegah Individualisme dalam Penetapan Dogma dan Moralitas Kristiani: Menjajaki Pemikiran Karl Barth - Virjinia Elizabeth Taunu; Yohanisa Meranti Ora; Juanto Runesi; Ebenhaizer Imanuel Nuban Timo (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2026)
This study aims to analyze the theological thought of Karl Barth as a conceptual foundation for responding to the tendency of religious individualism in modern Christianity. The shifting orientation of faith, which increasingly emphasizes subjective experience and a private relationship with God, is considered to have the potential to reduce the communal and ecclesial dimensions of Christian faith. This research employs a qualitative approach using a descriptive-analytical and constructive literature study method. Data were collected through the examination of primary and secondary sources and subsequently analyzed using content analysis and a theological hermeneutical approach to identify key themes within Barth’s theology. The findings indicate that the supremacy of God’s revelation in Christ, the concept of analogia relationis, as well as the understanding of humanitas Dei and the church as a community of witness, form a theological framework that systematically critiques subjectivism in faith and individualistic autonomy. In conclusion, Barth’s thought offers a theological paradigm that affirms the relational, communal, and social dimensions of Christian faith, calling the church to cultivate a spirituality rooted in divine revelation and embodied in shared responsibility within modern society.